Cinenurducation in Improving Communication Skills among Nursing Students - Ratna Wirawati Rosyida; Febriana Sartika Sari; Bayu Akbar Khayudin; Ni Kadek Diah Purnamayanti (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Introduction: Innovative and fun learning strategies can support the success of nursing education. Cinenurducation is one of the learning methods using interesting films and is expected to help students understand and improve communication skills. Aim: to find out the effectiveness of the application of cinenurducation on the communication skills of nursing students. Method: The research design was quasi-experimental with a one-group pretest-posttest with 30 respondents. The 4-week intervention included a review of the topic on nursing communication, watching 2 films once a week, accompanied by active discussion about the film related to communication skills. Communication Skills In Healthcare Professionals questionnaire to test communication skills before and after intervention. Data analysis was carried out using a dependent t-test. Results: The average age of the respondents was 20 years, GPA > was 3.5, 96.7% respondents were female, 26.7% were 5th semester students, and 70% had 0-3 months of practice experience, while the remaining had no clinical practice experience. The average difference before and after cinenurducation was 0.52 (SD=0.34). For each aspect of communication skills, the aspect with the highest average both before and after the application of cinenurducation was the attitude of mutual respect and respect which was 5 (SD=0.56) and 5.7 (SD=0.38), respectively. In addition, there was a significant difference before and after the intervention (p-value<0.05) for the total communication ability score. Conclusions: Cinenurducation effectively improves the communication skills of nursing students. For this reason, cinenurducation can be used as one of the teaching strategies in nursing.